Euforia Puncak Mas: Mengeksplorasi Kepuasan Wisatawan dan Memorable Tourism Experience dalam Menumbuhkan Minat Berkunjung Kembali - Nia Lefiani; Selvie Revirani (Journal of Tourism and Economic, 2024)
Based on the pre-survey that has been carried out, there are many complaints regarding the safety of rides and facilities and infrastructure that are incomplete and need improvement, such as lack of security at each ride. This research aims to find out how tourist satisfaction and memorable tourism experiences influence interest in returning to Puncak Mas. The population in this study were tourists who visited the Puncak Mas tourist destination, with a sample of 100 samples and the sampling technique used was the Accidental Sampling technique. This research uses the Partial Least Square 3.0 method. The results of this research are that tourist satisfaction does not directly influence interest in visiting again, tourist satisfaction influences Memorable Tourism Experience and Memorable Tourism Experience influences Interest in Returning.